URBAN FORESTRY IN MOGI GUAÇU, SÃO PAULO STATE, BRAZIL - Scanavaca Júnior, Laerte; Corrêa, Rony Felipe Marcelino (REVISTA DE AGRICULTURA, 2020)
This study evaluated urban forestry in Mogi Guaçu, São Paulo State, Brazil, according to purchasing power. Stratified sampling was carried out in five neighborhoods, totaling 75 blocks, enabling the identification of 57 species, 20 of which are native and 37 exotics. The frequency of exotic specimens was 77.15%. The three most frequent species (57.87%) had the highest phytosanitary occurrences. Small trees presented 63.13%, medium ones 29.33% and large trees with 7.54% of frequency. Mogi Guaçu had an average Green Area Index (GAI) of 10.85 m² per inhabitant, with good potential to increase at low cost, as there are many empty spaces and the replacement of trees that presented problems must be with large trees of native forest near the city. There was no correlation between purchasing power and GAI.